Susceptibility source separation from gradient echo data using magnitude decay modeling. Issue 5 (6th June 2022) - Dimov, Alexey V.; Nguyen, Thanh D.; Gillen, Kelly M.; Marcille, Melanie; Spincemaille, Pascal; Pitt, David; Gauthier, Susan A.; Wang, Yi
Abstract: Background and Purpose: The objective is to demonstrate feasibility of separating magnetic sources in quantitative susceptibility mapping (QSM) by incorporating magnitude decay rates R 2 ∗ $R_2^{\rm{*}}$ in gradient echo (GRE) MRI. Methods: Magnetic susceptibility source separation was developed using R 2 ∗ $R_2^{\rm{*}}$ and compared with a prior method using R 2 ′ = R 2 ∗ − R 2 ${R^{′}_2} = R_2^* - {R_2}$ that required an additional sequence to measure the transverse relaxation rate R 2 . Both susceptibility separation methods were compared in multiple sclerosis (MS) patients ( n = 17). Susceptibility values of negative sources estimated with R 2 ∗ $R_2^{\rm{*}}$ ‐based source separation in a set of enhancing MS lesions ( n = 44) were correlated against longitudinal myelin water fraction (MWF) changes. Results: In in vivo data, linear regression of the estimated χ + ${χ}^{+}$ and χ − ${χ}^{-}$ susceptibility values between the R 2 ∗ $R_2^*$ ‐ and the R 2 ′ ${R^{′}_2}$ ‐based separation methods performed across 182 segmented lesions revealed correlation coefficient r = .96 and slope close .99. Correlation analysis in enhancing lesions revealed a significant positive association between the χ − ${χ}^{-}$ increase at 1‐year post‐onset relative to 0 year and the MWF increase at 1 year relative to 0 year ( β = ‐0.144, 95% confidence interval: [–0.199, –0.1], p = .0008) and good agreement between R 2 ′ ${R^{′}_2}$ and R 2 ∗ $R_2^*$ methods ( r = .79, slope = .95). Conclusions: Separation of magnetic sources based solely on GRE complex data is feasible by combining magnitude decay rate modeling and phase‐based QSM and χ − ${χ}^{-}$ change may serve as a biomarker for myelin recovery or damage in acute MS lesions.